Properties of Nilpotent Evolution Algebras with no Maximal Nilindex (European Journal of Pure and Applied Mathematics, 2021)
As a system of abstract algebra, evolution algebras are commutative and non-associative algebras. There is no deep structure theorem for general non-associative algebras. However, there are deep structure theorem and classification theorem for evolution algebras because it has been introduced concepts of dynamical systems to evolution algebras. Recently, in [25], it has been studied some properties of nilpotent evolution algebra with maximal index (dim E2 = dim E âˆ’ 1). This paper is devoted to studying nilpotent finite-dimensional evolution algebras E with dim E2 =dim E âˆ’ 2. We describe Lie algebras related to the evolution of algebras. Moreover, this result allowed us to characterize all local and 2-local derivations of the considered evolution algebras. All automorphisms and local automorphisms of the nilpotent evolution algebras are found.